Quantum metrology of solid-state single-photon sources using photon-number-resolving detectors. (28th March 2019) - von Helversen, Martin; Böhm, Jonas; Schmidt, Marco; Gschrey, Manuel; Schulze, Jan-Hindrik; Strittmatter, André; Rodt, Sven; Beyer, Jörn; Heindel, Tobias; Reitzenstein, Stephan
Abstract: Quantum-light sources based on semiconductor quantum dots (QDs) are promising candidates for many applications in quantum photonics and quantum communication. Important emission characteristics of such emitters, namely the single-photon purity and photon indistinguishability, are usually assessed via time-correlated measurements using standard 'click' detectors in Hanbury Brown and Twiss or Hong-Ou-Mandel (HOM-) type configurations. In this work, we employ a state-of-the-art photon-number-resolving (PNR) detection system based on superconducting transition-edge sensors (TESs) to directly access the photon-number distribution of deterministically fabricated solid-state single-photon sources. Offering quantum efficiencies close to unity and high energy resolution, our TES-based two-channel detector system allows us to analyse the quantum optical properties of a QD-based non-classical light source. In particular, it enables the direct observation of the two-particle Fock-state resulting from interference of quantum mechanically indistinguishable photons in HOM-experiments. Additionally, comparative measurements reveal excellent quantitative agreement of the photon-indistinguishabilities obtained with PNR ((90 ± 7)%) and standard click ((90 ± 5)%) detectors. Our work thus demonstrates that TES-based detectors are perfectly suitable for the quantum metrology of non-classical light sources and higlights appealing prospects for the efficient implementation of quantum information tasks based on multi-photon states.